2021
DOI: 10.1371/journal.pone.0246030
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality of coronavirus disease-2019 (COVID-19) patients in two centers of Hubei province, China: A retrospective analysis

Abstract: Purpose Since the outbreak in late December 2019 in Wuhan, China, coronavirus disease-2019 (COVID-19) has become a global pandemic. We analyzed and compared the clinical, laboratory, and radiological characteristics between survivors and non-survivors and identify risk factors for mortality. Methods Clinical and laboratory variables, radiological features, treatment approach, and complications were retrospectively collected in two centers of Hubei province, China. Cox regression analysis was conducted to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
55
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 23 publications
(71 reference statements)
16
55
5
Order By: Relevance
“…Sensitivity analysis, performed by sequentially removing each study and re-assessing the pooled estimates, showed that the magnitude and the direction of the effect size were not influenced (effect size range, between 0.77 and 0.84) ( Figure 4 ). CK-MB concentrations remained statistically significantly higher (SMD 0.72, 95% CI 0.54 to 0.90, p<0.001; I 2 =90.2%, p<0.001) in patients with high severity or non-survivor status after excluding 5 relatively large studies that accounted for nearly 28% of the overall sample size [ 36 , 58 , 67 , 78 , 83 ].
Figure 4 Sensitivity analysis of the association between CK-MB and COVID-19 disease.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sensitivity analysis, performed by sequentially removing each study and re-assessing the pooled estimates, showed that the magnitude and the direction of the effect size were not influenced (effect size range, between 0.77 and 0.84) ( Figure 4 ). CK-MB concentrations remained statistically significantly higher (SMD 0.72, 95% CI 0.54 to 0.90, p<0.001; I 2 =90.2%, p<0.001) in patients with high severity or non-survivor status after excluding 5 relatively large studies that accounted for nearly 28% of the overall sample size [ 36 , 58 , 67 , 78 , 83 ].
Figure 4 Sensitivity analysis of the association between CK-MB and COVID-19 disease.
…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were conducted in Turkey [ 34 , 58 ], 1 in the USA [ 57 ], 1 in Korea [ 52 ], and the remaining 51 in China [ 14 , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [53] , [54] , [55] , [56] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] ]. Three studies were prospective [ 42 , 53 , 68 ], 47 retrospective [ [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies were retrospective [ 30 32 , 34 37 , 39 42 ], whilst the remaining two were prospective [ 33 , 38 ]. Endpoints included disease severity based on current clinical guidelines (8 studies) [ 31 , 33 35 , 37 , 39 , 40 , 42 ], disease progression (one study) [ 38 ] and occurrence of acute respiratory distress syndrome (ARDS) (one study) [ 36 ], and survival status (4 studies) [ 30 , 32 , 36 , 41 ]. Only two studies reported the presence of AKI [ 32 , 39 ].…”
Section: Resultsmentioning
confidence: 99%